The effects of low-intensity electromagnetic irradiation at the frequencies of 51.8 and 53 ghz and antibiotic ceftazidime on Lactobacillus acidophilus F0F1 ATP-ase activity - D. R. Soghomonyan (ՀՀ ԳԱԱ հրատ.)
The effects of low intensity electromagnetic irradiation (EMI) at the frequencies 51.8 and 53 GHz and antibiotic ceftazidime on N,N'-dicyclohexilcarbodiimide (DCCD), inhibited ATP-ase activity of Lactobacillus acidophilus membrane vesicles were investigated. Ուսումնասիրվել է ցածր ուժգնությամբ, 51,8 և 53 ԳՀց հաճախականությամբ էլեկտրամագնիսական ալիքների և հակաբիոտիկ ցեֆտազիդիմի ազդեցությունը Lactobacillus acidophilus կաթնաթթվային բակտերիաների թաղանթային բշտիկների, N'-դիցիկլոհեքսիլկարբոդիիմիդի (ԴՑԿԴ)նկատմամբ զգայուն ԱԵՖ-ազային ակտիվության վրա: Было изучено влияние низкоинтенсивных электромагнитных волн с частотами 51,8 и 53 ГГц и антибиотика цефтазидима на N,N'-дициклогексил карбодиимид (ДЦКД) чувствительную АТФ-азную активность мембранных везикул молочнокислых бактерий Lactobacillus acidophilus.
Keywords: Biology; Biophysics